Implementation of Zuhd in the Islâh Movement of Shaykh Abdul Qadir al-Jilani (D. 561 H./1161 CE.) - Nur Hadi Ihsan; Moh. Isom Mudin; Amir Sahidin (Jurnal Madania)
The issue of zuhd is very urgent to deal with, especially in the current era of modernization which has had negative impacts in all fields; in education, social, political, and cultural. Therefore, an islâh movement is needed to minimize and even eliminate these negative impacts. Among the Sufi scholars who were very persistent in implementing the islâh movement was Shaykh Abdul Qadir al-Jilani. At a time when there was a lot of depravity and shocks in his time, al-Jilani with his zuhd was able to play a good role in this islâh movement. Therefore, this article will specifically discuss the implementation of zuhd in the islâh movement of Shaykh Abdul Qadir al-Jilani. Using the descriptive-analytical method, this study finds that the implementation of zuhd in the islâh movement of al-Jilani includes three things, namely in interpreting the true meaning and understanding of zuhd; in education and teaching, as well as in his lectures and preaching. Thus, al-Jilani was one of the Sufi scholars who integrated the teaching of zuhd with his islâh movements. Finally, it seems justifiable to assert that integrating zuhd with the islâh movement is very important to overcome the destructive impacts of modernization.